RESPON PERTUMBUHAN DAN HASIL JAGUNG MANIS (Zea mays saccharata) PADA BERBAGAI WAKTU PEMBERIAN PUPUK NITROGEN DAN KETEBALAN MULSA JERAMI - Muhammad Sirajuddin; Sri Anjar Lasmini (Universitas Tadulako, 2010)
This research was conducted on February to May 2009 in Jonooge village, Biromaru sub district Sigi regency Central Sulawesi province. A 3x3 factorial experiment in a randomized block design was used. The first factor was nitrogen fertilizer 200 kg N/ha applied at different times and rates: single application at sowing (W1), 1/3 rate at sowing and 2/3 rate at 15 d after sowing (W2), 1/3 rate at sowing and 2/3 at 30 d after sowing (W3), and 1/3 rate at sowing and 2/3 at 45 d after sowing (W4). The second factor was thickness of mulch: 3 cm (J1), 5 cm (J2) and 7 cm (J3). The research results showed that there was no interaction effect between nitrogen fertilizer applications and mulch thickness. Better plant height (164.78 cm), weight of 10 corncobs (2.43 kg), girth (7.70 cm), number of kernel rows, and corncob length (18.3 cm) was found in treatment W3 than the other nitrogen fertilizer treatments. Mulch added at 7 cm thickness resulted in larger sugar content (26.55%), plant height (166.94 cm), and weight of 10 corncobs than the other mulch treatment